Effect of Job Motivation, Job Satisfaction and Work Environment on Employee Performance (Case Study at PT Kalbe Farma Tbk Jakarta) - boris - (Perbanas Institute, 2021)
Introduction. Based on previous research conducted by Bachtiar (2012) and Reza (2010), according to Rahmawati (2011), Widyanti et al (2015) and Timothy (2017) there are differences in research results, so this study aims to analyze the effect of work motivation, job satisfaction, and work environment on employee performance. Research methods. The population in this study were all 60 employees of PT Kalbe Farma Tbk Jakarta Global Supply Chain division. The sampling used is saturated sampling where the entire population is used as a sample so that the number of research samples is 60 people. Data analysis. The analysis technique used is multiple linear regression. Findings. Based on the results of the study, partially work motivationand job satisfaction have a significant positive effect on employee performance, while the work environment has no effect on employee performance. Adjusted R Square of 0.854 which means that employeeperformance is influenced by work motivation, job satisfaction and work environment with a percentage of 85.4% and the remaining 14.6% is influenced by other factors, Recommendation. It is recommended for further researchers to add independent variables.